Low-cost Design and Manufacturing of Surgical Guides for Mandibular Reconstruction Using a Fibula. Issue 7 (July 2016) - Numajiri, Toshiaki; Nakamura, Hiroko; Sowa, Yoshihiro; Nishino, Kenichi
Abstract : Background: Surgical cutting guides are used in mandibular reconstruction involving osteotomy of the mandible and fibula. Cutting guides produced using computer-aided design (CAD) and computer-aided manufacturing (CAM) technologies have been reported recently. These guides aim to increase the benefits to patients by improving the accuracy, shortening the operating time, and correcting occlusion. However, the availability of these advanced technologies is limited in some regions of the world. To test whether we could produce low-cost surgical cutting guides, we made surgical guides and investigated their accuracy. Methods: Using free CAD software, we designed surgical cutting guides for the mandible and fibula and used these to perform virtual mandibular segmental osteotomies and fibula transplants in 12 model surgeries. The cutting guides were printed on a 3-dimensional (3D) printer. The model surgeries were performed using 3D mandibular models and cutting guides to check their accuracy. Deviations between the virtually simulated plan and the actual model surgery were investigated. Results: CAD and CAM technologies were used to design and 3D print the cutting guides and models. The guided surgeries were performed. The deviations were about 1.3 mm for mandibular osteotomy, less than 1 mm for fibular osteotomy, and within 2.4 mm for reconstructions of the mandible. Conclusions: Without using expensive software or products, we were able to design surgical cutting guides for the mandible and fibula and used these to perform virtual simulation of mandibular segmental osteotomy and fibular reconstruction. Model surgeries using 3D-printed surgical guides showed that the accuracy of reconstruction was within a 3-mm deviation. In circumstances where commercial CAD/CAM guides are not available, it may be possible to use CAD/CAM surgical guides in the clinic if doctors are willing to volunteer their time for the design and printing.